A Healthier Future for Tissue Viability - An initiative to improve outcomes for patients with lower limb issues. Issue 4 (November 2021) - Sandoz, Heidi; Walton, Suzanne
Abstract: Reducing unwarranted variation in clinical care and access to care was a central goal of the Five Year Forward View, and the later Long Term Plan. Variation in provision and access to lower limb services in one Sustainability and Transformation Partnership were apparent. Through networking and collaboration of STP wide tissue viability and related specialist services a programme of service development was accepted as part of wider Frailty service provision. This led to a public health needs assessment of the problem being commissioned; 6 clinical pathways being produced; and clear recommendations for improvement in service provision being made. The public health needs assessment is believed to be the first of its kind considering the issues of leg ulceration, cellulitis of the lower limb, lymphoedema of the lower limb (excluding cancer related), chronic oedema of the lower limb, diabetic foot ulceration and foot ulceration. Data from local hospital episode statistics, community services data and extrapolation from national data sources has been used to understand the local impact. This provided an idea of the numbers of the population affected, the costs to the local health economy and a baseline for improvement outcome measurement in the future. It also prompted widespread service provision changes to meet the needs of those living with lymphoedema and chronic oedema and pathways for skin tear and leg ulceration have been designed for implementation. The public health needs assessment is fully published and freely accessible elsewhere. This article describes the process followed to undertake the work. Highlights: A public health needs assessment of lower limb oedema, ulceration and cellulitis. Local population costs related to lower limb conditions using inpatient spell data. Building the foundations for sustainability and transformation in lower limb care. A clinician led collaborative to reduce unwarranted variation in access to care. Providing a baseline of lower limb data for quality improvement outcome measures.